Respuesta :

The function for a is (f o g) (x) = 8x^2-10.



Explanation

=========================
[tex]f(x)=2x-4, g(x)=4x^2-3, (f o g)=f(g(x))[/tex]  

I already knew that the g of x is equal to [tex]4x^2-3[/tex] so I substitute inside of the g of x

[tex]g(x)=4x^2-3[/tex] =======> [tex]f(x)=4x^2-3[/tex] =============> [tex]2(4x^2-3)-4[/tex] 

simplify it 
 
[tex]2(4x^2-3)-4[/tex]  =======> [tex]8x^2-6-4[/tex] =========> [tex]8x^2-10[/tex]

[tex](f o g) = 8x^2-10[/tex]


(fоg)(x)=f(g(x))
=f(4x^2-3)
=2(4x^2-3)-4
=8x^2-6-4
=8x^2-10
ACCESS MORE